Interaction Design in eGov systems: challenges for a developing country - Hornung, Heiko; Baranauskas, M. Cecília C. (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2007: Anais do XXXIV Seminário Integrado de Software e Hardware, 2007)
Electronic government (eGov) systems can be fundamental instruments of citizens' access to knowledge. The term eGov emerged from the use of the internet, and – although not limited to it – constitutes an area of research and development whose practitioners face the challenges of the internet as a means of creative implementation of new systems and relationships between government and citizens. Today, we are facing a situation in Brazil that is characterized by vast differences with regard to socioeconomics, culture, geographical region differences as well as access to technology and knowledge. The big challenge to change this reality lies in the search for methods and system designs that facilitate access and support the formation of a digital culture that respects the diversity of our society. Starting from results of a literature research, this article investigates interaction design in eGov systems, pointing out some lessons learned as recommendations for the Brazilian context.